Some Aspects of Pharmacotoxicity of Amphetamine In Rats( Rattus rattus ) - Ahmed, Abdel Bagi Mustafa (Sudan University of Science and Technology, 2009)
Amphetamines are indirect sympathomimetic amines with potent stimulant action on central nervous system. These compounds produce tolerance and dependence. Full exploitation of amphetamine toxicity in man and animal is still lacking. Therefore, this study was carriedout to investigate some of the pharmacotoxicity of amphetamine in rats. Administration of 8mg/kg of amphetamine sulphate orally to rats for a month produced signs of restlessness and hyperexcitability and caused decreased activity of liver glutamic oxaloacetate and pyruvic oxaloacetate transaminases compared to controls. Marginal effects were observed in haematological and serobiochernical parameters. Amphetamine given for 60 days to rats significantly cused decreased activity of marker testicular enzyme such as sorbitol dehydrogenase and acid phosphatase but the activity of testicular lactic dehydrogenase, gamma-glutamyl trans peptidase and beta glucurinidase were significantly increased. A decrease in epididymal sperm count and motility and increased in percentage spermatozoa abnormality was also noticed. Further, daily intraperitoneal administration of d-amphetamine sulphate at a dose of 8 mg/kg, body weight to rats during 6-15 days of gestation has resulted in significant effect on sensory and motor reflexes of their pups. These pups have shown increased righting and rotating reflexes and cliff avoidance activity. Significant increase in brain norademaline, 5-hydroxytryptamine and decrease in monoamine oxidase activity was observed in these pups and their mothers compared to their control counterparts. These results show that the amphetamine was toxic to rats at the dose of 8mg/kg producing mild, hepatotoxicity, testicular atrophy indicated in decreased sperm count and sperm abnormalities, increased brain catecholamine that was associated with hyperexcitability and causing disturbed behavioural activity in the neonates. Thesis Sudan University of Science and Technology